1980
DOI: 10.1007/bf01324273
|View full text |Cite
|
Sign up to set email alerts
|

Microcalorimetric investigations of the metabolism of yeasts VII. Flow-calorimetry of aerobic batch cultures

Abstract: The heat evolution of aerobic batch cultures of growing yeast (Saccharomyces cerevisiae) in glucose media was investigated by a combination of a flow-microcalorimeter with a fermentor vessel. The course of heat production, cell production and the rate of oxygen consumption were qualitatively the same for all glucose concentrations between 10 mM and 100 mM. Under optimal aerobic conditions a triphasic growth was observed due to the fermentation of glucose to ethanol, respiration of ethanol to CO2 and acetate, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

1981
1981
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 9 publications
3
5
0
Order By: Relevance
“…For glucose-grown cells, the specific activity of GPDH was ca. 20 mU/mg of protein during the respirofermentative phase ( 6.0 throughout growth, the overall heat production per biomass formation for respiratory-phase cells was 30.2 J/mg (dry weight) formed (6). This is in accordance with the value of dQ/dX for E/R1 ( Table 2).…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…For glucose-grown cells, the specific activity of GPDH was ca. 20 mU/mg of protein during the respirofermentative phase ( 6.0 throughout growth, the overall heat production per biomass formation for respiratory-phase cells was 30.2 J/mg (dry weight) formed (6). This is in accordance with the value of dQ/dX for E/R1 ( Table 2).…”
Section: Resultssupporting
confidence: 84%
“…1), which explains the decrease in fermentation. Glucose was exhausted between G/T and G/Rl, in contradiction to the results of Brettel et al (6), who reported glucose to be exhausted at the apex in the heat production rate curve prior to G/T. The respiratory activity is subject to glucose repression (12) and was not fully expressed until point G/R2 (Fig.…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…Brettel et al reported that the metabolic and growth rate of S. cerevisiae remained almost constant in dextrose levels between 0.16 to 1.6% [42]. S. cerevisiae does switch to respiratory metabolism when the medium is depleted of dextrose, but it appears that the cells must actually be starved of dextrose before they undergo a diauxic shift [12].…”
Section: Discussionmentioning
confidence: 99%
“…This heat represents the free energy dissipated irreversibly during metabolism, providing an all-inclusive measure of metabolic activity. We built up on previous studies on yeast microcalorimetry [7][10] [11], and by applying state of the art electronics for data acquisition and analysis, highly accurate reproductive data were obtained with our flow microcalorimetry set-up. As opposed to previous studies in which prototrophic strains were used [7] [6], we analyze an auxotrophic strain (BY4741) that is commonly used in laboratory studies [12].…”
Section: Introductionmentioning
confidence: 99%